Impact of leadership training and team development on academic chairs - Kathleen O'Rourke; Tim Miller (Academic Chairpersons Conference Proceedings, 2015)
The challenges for chairpersons are many: establishing relationships that capitalize on strengths of faculty, maximizing trust and credibility, focusing teams on critical priorities, and aligning values that support the organization’s vision and mission. This case study demonstrates how leadership training provided necessary tools for a chair to accomplish these task
Keywords: Trust & amp; credibility; purpose and intent; respect for different styles